Expatriates Coaching Behaviors and Local Employees Work Performance: Mediating Role of Cross - Cultural Knowledge Transfer - Windy Lau Edwin Pasadame; Xiongying Niu (Eduvest - Journal of Universal Studies, 2021)
This study investigates How the coaching behavior of Chinese expatriates and the performance of local employees overcomes the inherent differences between them and develops the quality of relationships that play an important role in carrying out cross-cultural knowledge transfer? Existing research does not provide a good answer to this question. The knowledge transfer literature has focused on organizational vehicles and structural mechanisms, with little attention paid to understanding how the organizational processes and individuals involved can facilitate knowledge transfer. After all, it is people who have applied and transferred knowledge. This study aims to propose and analyze a model for developing expatriate coaching behavior through cross-cultural knowledge transfer in improving the work performance of local employees, to examine the moderating role of intelligence culture for expatriate coaching behavior on the relationship of cross-cultural knowledge transfer to local employee performance on expatriates and employees. This study will examine the moderating role of Perceived Organizational Support theorists have suggested that employees form global perceptions of the level of support provided by their employers and that this perception influences their behavior in the workplace. The data collection method used is a qualitative method. Based on the results of research and discussion, it can be concluded that China expatriates with high cultural intelligence, their coaching behavior has a clearer positive impact on the performance of local employees; for local employees who have high cultural intelligence, expatriate coaching behavior has a clearer positive impact on the employee's performance.